Unstretched polyethylene film and preparation method thereof
By adopting an unstretched polyethylene film with a four-layer composite structure, the problem of insufficient adhesion of the aluminum layer during the molding laser aluminum plating process is solved, and the molding laser aluminum plating effect with high adhesion and high composite peel strength are achieved, which improves the environmental protection performance and recyclability of the packaging materials.
Patent Information
- Application Number
- CN202510097984.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
AI Technical Summary
The existing polyethylene films lack adhesion of the aluminum layer during the molding laser aluminum plating process, which leads to the aluminum layer falling off, affecting the aesthetics and anti-counterfeiting effect of the product. At the same time, the composite peel strength between the PET laser film and the PE film is insufficient, limiting the application of a single material packaging solution.
The unstretched polyethylene film adopting a four-layer composite structure includes a non-laser molded layer, a first intermediate layer, a second intermediate layer and an information molded aluminum-plating layer. By precisely controlling the material ratio and processing temperature, a molded laser aluminum-plating effect is achieved with high adhesion.
It improves the environmental performance and recyclability of the film, realizes the high adhesion molded laser aluminum plating effect, replaces the traditional PET laser film, meets the packaging requirements of high composite peel strength, and reduces environmental pollution.
Smart Images

Figure CN119872042A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of film materials for packaging, and more specifically, to an unstretched polyethylene film and a preparation method thereof. Background Art
[0002] In the field of packaging materials, especially in the application of plastic films, laser films are usually used as part of packaging materials in order to achieve the aesthetic and anti-counterfeiting requirements of products. Traditional laser films are mostly made of PET (polyethylene terephthalate) materials. Although this material has good optical properties and anti-counterfeiting characteristics, it is difficult to achieve a single material packaging solution due to its poor compatibility with polyethylene (PE) materials. At the same time, after compounding, its composite peel strength does not meet the requirements of special products, which not only affects the recycling and reuse of materials, but also increases the environmental burden. At the same time, it cannot meet the packaging requirements of special products for relatively high composite peel strength. In addition, in the existing technology, when polyethylene films are molded laser aluminum plating, it is often difficult to achieve ideal aluminum adhesion and peel strength, which limits its application in the field of high-end packaging.
[0003] In the process of implementing the embodiments of the present invention, the inventors found that there are at least the following problems or defects in the prior art: the existing polyethylene film cannot be directly molded and laser-plated with aluminum, or the aluminum layer has insufficient adhesion after aluminum plating, which leads to the problem of aluminum layer falling off easily during subsequent use, affecting the appearance and anti-counterfeiting effect of the product. At the same time, due to the insufficient composite peeling strength of PET laser film and PE film, its application in single-material packaging solutions is limited. Summary of the invention
[0004] The invention provides an unstretched polyethylene film and a preparation method thereof.
[0005] In a first aspect of the present invention, there is provided an unstretched polyethylene film, comprising a four-layer composite structure, which are respectively a non-laser molded layer, a first intermediate layer, a second intermediate layer, and an information molded aluminum-plated layer; The non-laser molded layer comprises high-pressure polyethylene, linear polyethylene, metallocene polyethylene and anti-blocking agent, and the mass percentage of the manufacturing components is: 10%-30% of high-pressure polyethylene, 20%-50% of linear polyethylene, 10%-30% of metallocene polyethylene and 4%-7% of anti-blocking agent that does not affect haze; The first intermediate layer and the second intermediate layer are made of the same material, and the components include high-pressure polyethylene, low-pressure polyethylene, and linear polyethylene, and the mass percentage of the manufacturing components is: high-pressure polyethylene 10%-20%, low-pressure polyethylene 5%-25%, metallocene polyethylene 20%-50%, and easy processing aid 0.5%-1%; The information molded aluminum-plated layer comprises high-pressure polyethylene, metallocene polyethylene, an anti-adhesive agent that does not affect haze, and special additives, and the mass percentages of the manufacturing components are: 5%-20% high-pressure polyethylene, 5%-10% linear polyethylene, 50%-90% metallocene polyethylene, 4%-8% anti-adhesive agent that does not affect haze, and 2%-8% special additives.
[0006] Furthermore, the thickness ratios of the non-laser molded layer, the first intermediate layer, the second intermediate layer and the information molded aluminum film layer are: 20-30% for the non-laser molded layer, 20-35% for the first intermediate layer, 20-35% for the second intermediate layer, and 20-30% for the information laser molded aluminum layer.
[0007] Furthermore, the main component of the anti-adhesion agent is organic synthetic silicon micro-spherical particles.
[0008] Further, if barrier properties are required, the non-laser embossed layer may be barrier coated.
[0009] Furthermore, the aluminum-plated substrate based on the unstretched polyethylene film is characterized in that it includes the unstretched polyethylene film and an aluminum film layer, and the aluminum film layer is combined with the corona layer of the film.
[0010] In a second aspect of the present invention, a method for preparing an unstretched polyethylene film is provided, which specifically comprises the following steps: S1. Prepare the raw materials of each layer component and stir them evenly, then heat and plasticize them to melt the raw materials, and then extrude the plasticized resin forward through the screw of the extruder, and extrude and laminate through the T-die according to the designed structural level, wherein the processing temperature of heating and plasticizing and the T-die is 165℃-245℃; S2. The extruded resin passes through the T-type die head and flows to the primary cold roller, where it is cooled and formed by the secondary cold roller; S3. Detect and control the thickness of the formed film; S4. Then roll it up and perform aging treatment.
[0011] Furthermore, the stirring time of each layer of raw materials in step S1 is 15-30 minutes.
[0012] Furthermore, in step S2, the temperature of the primary cold roller is 15-30°C, and the temperature of the secondary cold roller is 10-20°C.
[0013] Furthermore, in step S3, a β-ray thickness gauge is used to detect the thickness of the film, and the detection accuracy is ±0.001 mm.
[0014] Furthermore, the aging treatment time in step S4 is 24-48 hours, the treatment environment temperature is 20-30° C., and the relative humidity is 40%-60%.
[0015] According to the above embodiments of the present invention, at least the following beneficial effects are achieved: the unstretched polyethylene film and the preparation method thereof provided by the present invention can improve the environmental performance and recyclability of the film. By adopting a specific four-layer composite structure and accurately controlling the material ratio, the film can achieve a high-adhesion molded laser aluminum plating effect without using a PET laser film, thereby replacing the traditional PET laser film and achieving a single-material polyethylene film. This film not only has good optical properties and anti-counterfeiting properties, but is also more convenient in the recycling process, can reduce environmental pollution, and is in line with the current trend of environmental protection and sustainable development.
[0016] In addition, the unstretched polyethylene film of the present invention adopts a specific processing temperature and cooling molding process during the preparation process, which can effectively control the thickness and quality of the film and ensure the uniformity and stability of the film. At the same time, through accurate thickness detection and aging treatment, the high performance and reliability of the film can be further ensured. This film preparation method can not only improve production efficiency and reduce costs, but also provide a new solution for the high-end packaging material market and enhance the market competitiveness of products. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The above and other objects, features and advantages of the exemplary embodiments of the present invention will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present invention are shown in an exemplary and non-limiting manner, in which: Figure 1 A schematic flow chart of a method for preparing an unstretched polyethylene film provided in one embodiment of the present invention. DETAILED DESCRIPTION
[0018] The principles and spirit of the present invention will be described below with reference to several exemplary embodiments. It should be understood that these embodiments are provided only to enable those skilled in the art to better understand and implement the present invention, and are not intended to limit the scope of the present invention in any way. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0019] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. All features disclosed in this specification, or steps in all methods or processes disclosed, except for mutually exclusive characteristics and / or steps, can be combined in any way, unless otherwise described, and can be replaced by other equivalent or alternative features with similar purposes, that is, unless otherwise described, each feature is only one embodiment in a series of equivalent or similar features.
[0020] In some embodiments, an unstretched polyethylene film includes a four-layer composite structure, which are, in order, a non-laser molded layer, a first intermediate layer, a second intermediate layer, and an information molded aluminum-plated layer; The non-laser molded layer comprises high-pressure polyethylene, linear polyethylene, metallocene polyethylene and anti-blocking agent, and the mass percentage of the manufacturing components is: 10%-30% of high-pressure polyethylene, 20%-50% of linear polyethylene, 10%-30% of metallocene polyethylene and 4%-7% of anti-blocking agent that does not affect haze; The first intermediate layer and the second intermediate layer are made of the same material, and the components include high-pressure polyethylene, low-pressure polyethylene, and linear polyethylene, and the mass percentage of the manufacturing components is: high-pressure polyethylene 10%-20%, low-pressure polyethylene 5%-25%, metallocene polyethylene 20%-50%, and easy processing aid 0.5%-1%; The information molded aluminum-plated layer comprises high-pressure polyethylene, metallocene polyethylene, an anti-adhesive agent that does not affect haze, and special additives, and the mass percentages of the manufacturing components are: 5%-20% high-pressure polyethylene, 5%-10% linear polyethylene, 50%-90% metallocene polyethylene, 4%-8% anti-adhesive agent that does not affect haze, and 2%-8% special additives.
[0021] It should be noted that the four-layer composite structure of the unstretched polyethylene film is composed of a non-laser molded layer, a first intermediate layer, a second intermediate layer and an information molded aluminum-plated layer. Here, the unstretched polyethylene film refers to a polyethylene film that has not been mechanically stretched during the production process. This film has important applications in the field of packaging materials due to its structural characteristics. The non-laser molded layer refers to a polyethylene layer that does not contain a laser effect, and is mainly used for the outermost layer of the film to provide protection and decorative functions.
[0022] Specifically, the ingredients of the non-laser molded layer include high-pressure polyethylene, linear polyethylene, metallocene polyethylene and anti-blocking agent. High-pressure polyethylene is a polyethylene with a higher molecular weight, which has higher strength and toughness; linear polyethylene has better ductility and impact resistance; metallocene polyethylene is a polyethylene produced using metallocene catalysts, which has a narrower molecular weight distribution and better processing performance; anti-blocking agent is used to prevent adhesion between film layers. The mass percentages of these ingredients are 10%-30% for high-pressure polyethylene, 20%-50% for linear polyethylene, 10%-30% for metallocene polyethylene and 4%-7% for anti-blocking agent. These parameters can be adjusted according to specific product requirements and performance goals.
[0023] Preferably, the specific proportion of high pressure polyethylene in the non-laser molded layer can be set to 20%, linear polyethylene to 40%, metallocene polyethylene to 25%, and anti-blocking agent to 5%, so as to achieve ideal physical properties and processing properties. For the first intermediate layer and the second intermediate layer, their preparation materials are the same, and the components include high pressure polyethylene, low pressure polyethylene, linear polyethylene, and easy processing aids.
[0024] Furthermore, the mass percentages of these components can be adjusted to 15% high-pressure polyethylene, 15% low-pressure polyethylene, 30% linear polyethylene and 1% easy-processing aid to ensure the processing performance and interlayer bonding of the film. For the information molded aluminum layer, the preferred component ratio can be 10% high-pressure polyethylene, 8% linear polyethylene, 70% metallocene polyethylene, 6% anti-blocking agent and 5% special additive to ensure the adhesion of the aluminum layer and the overall performance of the film. These ratios can be fine-tuned according to actual production conditions and product performance requirements.
[0025] In some embodiments, the thickness ratios of the non-laser molded layer, the first intermediate layer, the second intermediate layer and the information molded aluminum film layer are: 20-30% for the non-laser molded layer, 20-35% for the first intermediate layer, 20-35% for the second intermediate layer, and 20-30% for the information laser molded aluminum film layer.
[0026] It should be noted that barrier coating is a technology that applies special materials on the surface of the film to improve the film's barrier properties to gas, moisture and light, thereby extending the shelf life of the packaged contents. This technology is particularly important for packaging applications that require high barrier properties.
[0027] Specifically, the mass percentage of the manufacturing components of the non-laser molded layer is 10%-30% high-pressure polyethylene, 20%-50% linear polyethylene, 10%-30% metallocene polyethylene, and 4%-7% anti-blocking agent that does not affect the haze. The ratio of these ingredients can be adjusted according to the specific application requirements of the film. For example, if the strength of the film needs to be improved, the proportion of high-pressure polyethylene can be appropriately increased; if the transparency of the film needs to be improved, the proportion of linear polyethylene can be appropriately adjusted. In addition, the selection of anti-blocking agents is crucial to maintaining the surface properties of the film and preventing interlayer adhesion. Its main component can be organic synthetic silicon microspherical particles, which have good anti-blocking effects due to their unique surface properties.
[0028] Preferably, the specific composition ratio of the non-laser molded layer can be set to 25% high-pressure polyethylene, 35% linear polyethylene, 20% metallocene polyethylene and 5% anti-blocking agent, which can provide good physical properties and processing performance. For barrier coating applications, a thin layer of silicon oxide or polyvinyl alcohol can be applied on the non-laser molded layer. These materials can effectively block oxygen and moisture while maintaining the transparency and surface characteristics of the film.
[0029] Furthermore, the thickness of the barrier coating can be adjusted according to the desired barrier effect, and the common thickness range is between 0.5 microns and 1 micron. In actual production, the best barrier coating solution can be determined based on specific packaging requirements and cost-benefit analysis.
[0030] In some embodiments, the anti-adhesive agent is mainly composed of organic synthetic silicon micro-spherical particles.
[0031] It should be noted that anti-adhesion agent refers to a substance added to polyethylene film to prevent the film layers from sticking to each other. The main component of this anti-adhesion agent is organic synthetic silicon microsphere particles, which is a man-made silicon-based material with excellent anti-adhesion properties due to its spherical shape and smooth surface.
[0032] Specifically, the use of anti-blocking agents in polyethylene films is to provide isolation between film layers to prevent adhesion during processing or use. Organic synthetic silicon microspheres can effectively reduce friction and adhesion between film layers due to their chemical inertness and physical properties. The size, shape and surface treatment of such particles can be customized according to specific application requirements. In the formulation of polyethylene film, the amount of anti-blocking agent added needs to be precisely controlled to ensure that the processing properties of the film are not affected and the expected anti-blocking effect can be achieved.
[0033] Preferably, the amount of anti-blocking agent added can be adjusted according to the specific application and processing conditions of the film. For example, in applications requiring higher anti-blocking performance, the addition ratio of organic synthetic silicon microsphere particles can be increased, or particles with smoother surfaces can be selected to improve the anti-blocking effect.
[0034] More specifically, the amount of anti-blocking agent added can be controlled between 4% and 7% of the total mass to ensure that the film has good processing properties and performance. As an alternative, other types of anti-blocking agents, such as nano-scale silica or other organosilicon compounds, can also be explored, which can also provide good anti-blocking effects and may bring additional performance advantages, such as improving the optical properties of the film or increasing the heat resistance of the film.
[0035] In some embodiments, the non-laser embossed layer may be barrier coated if barrier is desired.
[0036] It should be noted that barrier coating is a technology that applies special materials on the surface of the film to improve the film's barrier properties to gas, moisture and light, thereby extending the shelf life of the packaged contents. This technology is particularly important for packaging applications that require high barrier properties.
[0037] Specifically, barrier coating can be achieved by applying a special coating on the non-laser molded layer, which can be a metal oxide, polyvinyl alcohol or other polymer material. These materials can effectively block oxygen and moisture while maintaining the transparency and surface properties of the film. The thickness of the barrier coating can be adjusted according to the desired barrier effect, and the common thickness range is between tens of nanometers and several microns. In the formulation of polyethylene film, the material selection and thickness setting of the barrier coating need to be precisely controlled to ensure that the processing performance of the film is not affected and the expected barrier effect can be achieved.
[0038] Preferably, the barrier coating material can be selected from aluminum oxide or silicon oxide, which have good barrier properties and chemical stability. More specifically, the thickness of the barrier coating can be controlled between 0.05 microns and 0.5 microns to ensure that the film has good barrier properties without sacrificing transparency. As an alternative, a barrier coating with a multi-layer composite structure can also be used, for example, multiple layers of different materials are sequentially coated on the surface of a polyethylene film to achieve a more efficient barrier effect.
[0039] Furthermore, the barrier coating process can be performed at any stage during the film production process, such as after the film is formed or in subsequent processing, depending on the arrangement of the production equipment and process flow.
[0040] In some embodiments, an aluminum-plated substrate based on an unstretched polyethylene film includes an unstretched polyethylene film and an aluminum film layer, wherein the aluminum film layer is combined with a corona layer of the film.
[0041] It should be noted that an aluminized substrate of an unstretched polyethylene film comprises an unstretched polyethylene film and an aluminum film layer, wherein the aluminum film layer is combined with a corona layer of the film. Here, the corona layer refers to a surface layer formed on the polyethylene film during a specific treatment process, which has the property of increasing adhesion, so that the aluminum film can be firmly adhered to the polyethylene film. The aluminized substrate of this structure can be used to improve the barrier properties and aesthetics of the film.
[0042] Specifically, the aluminum film layer is formed by depositing aluminum material onto the corona layer of the polyethylene film through vacuum coating or other coating techniques. The treatment of the corona layer can increase the roughness and polarity of the film surface, thereby improving its bonding with the aluminum film layer. The thickness of the aluminum film layer can be adjusted according to the required barrier properties and aesthetic effects, and the common thickness range is between tens of nanometers and hundreds of nanometers. In actual production, the parameter settings of the corona treatment and aluminum plating process need to be optimized according to specific product requirements and performance goals.
[0043] Preferably, the corona treatment can be directly performed on the production line of the polyethylene film, and the surface of the film is treated by the corona treatment equipment to form a corona layer suitable for aluminum plating. More specifically, the power, frequency and treatment time of the corona treatment can be adjusted according to the material of the film and the required surface characteristics.
[0044] Furthermore, as an alternative, in addition to vacuum coating technology, other coating technologies such as magnetron sputtering or chemical vapor deposition can also be considered to form the aluminum film layer, which may provide better coating uniformity and adhesion. In addition, the thickness of the aluminum film layer can be optimized to about 100 nanometers to achieve a balance between good barrier properties and economy. In some applications, a protective layer or a printed layer can be further coated on the aluminum film layer to enhance the product's protective properties or improve the visual effect.
[0045] In some embodiments, the method for preparing the unstretched polyethylene film is as follows: Figure 1 As shown, the following steps are included: S1. Prepare the raw materials of each layer component and stir them evenly, then heat and plasticize them to melt the raw materials, and then extrude the plasticized resin forward through the screw of the extruder, and extrude and laminate through the T-die according to the designed structural level, wherein the processing temperature of heating and plasticizing and the T-die is 165℃-245℃; S2. The extruded resin passes through the T-type die head and flows to the primary cold roller, where it is cooled and formed by the secondary cold roller; S3. Detect and control the thickness of the formed film; S4. Then roll it up and perform aging treatment.
[0046] It should be noted that unstretched polyethylene film refers to a polyethylene film that has not been mechanically stretched during the production process. This film has important applications in the field of packaging materials due to its structural characteristics. The T-die is a device used in the extrusion process to extrude and overlap multiple layers of materials according to the designed structural hierarchy. It is crucial to form the layered structure of the film.
[0047] Specifically, step S1 of the preparation method includes evenly stirring the raw material ingredients of each layer component, then heating and plasticizing to melt the raw materials, and then extruding the plasticized resin forward through the screw of the extruder, and extruding and laminating through the T-die according to the designed structural hierarchy. The processing temperature of heating and plasticizing and the T-die is 165℃-245℃. This temperature range ensures that the polyethylene material can be fully melted and has good fluidity, while avoiding the decomposition of the material that may be caused by excessively high temperatures. In step S2, after the extruded resin flows through the T-die, it will flow to the main cold roller and be cooled and formed by the secondary cold roller. This process is crucial to controlling the thickness and physical properties of the film.
[0048] Preferably, in step S3, a β-ray thickness gauge can be used to detect the thickness of the film with a detection accuracy of ±0.001 mm to ensure the uniformity and quality of the film. In step S4, the aging treatment time is 24-48 hours, the treatment environment temperature is 20-30°C, and the relative humidity is 40%-60%. This step helps to eliminate the stress inside the film and improve its stability and durability.
[0049] More specifically, the aging treatment can be carried out in an environment with controlled humidity and temperature to ensure that the film completes the aging treatment under optimal conditions. As an alternative, in addition to the β-ray thickness gauge, an ultrasonic thickness gauge or an X-ray thickness gauge can also be used to detect the film thickness. These methods each have their own advantages, and the most appropriate detection method can be selected according to the specific production conditions and equipment capabilities.
[0050] In some embodiments, the stirring time of each layer of raw materials in step S1 is 15-30 minutes.
[0051] It should be noted that raw material mixing refers to the process of mixing raw materials of different components evenly, which is a key step to ensure uniform distribution of each layer of the film and consistent performance of the final product. Time here refers to the duration of the mixing process.
[0052] Specifically, claim 7 states that in step S1, the mixing time of each layer of raw materials is 15-30 minutes. This time range is based on experiments and production experience, and is intended to ensure that the raw materials are mixed evenly while avoiding excessive mixing that causes material performance degradation. The selection of mixing time depends on factors such as the type of raw materials, the type and speed of the agitator, and the initial state of the raw materials.
[0053] Preferably, the stirring time can be set to 20 minutes, which is a middle value in the range of 15-30 minutes, and generally can provide a good mixing effect. More specifically, a high-speed stirrer can be used in the stirring process to improve efficiency, while keeping the stirrer clean and maintained to ensure the consistency of the stirring effect.
[0054] Furthermore, as an alternative, a continuous stirring system can also be used, which can continuously stir the raw materials before adding them to the extruder to ensure that the raw materials are always evenly mixed throughout the extrusion process. In addition, the viscosity and temperature of the raw materials can be monitored online to adjust the stirring time for more precise process control.
[0055] In some embodiments, in step S2, the temperature of the primary cold roller is 15-30°C, and the temperature of the secondary cold roller is 10-20°C.
[0056] It should be noted that the primary cold roll and the secondary cold roll refer to the two rolls used to cool the film after extrusion. Their temperature has an important influence on the final physical properties and appearance of the film. The primary cold roll usually refers to the first cooling roll that contacts the molten resin, while the secondary cold roll refers to the subsequent cooling roll. The two work together to ensure uniform cooling of the film.
[0057] Specifically, claim 8 states that in step S2, the temperature of the primary cold roller should be controlled at 15-30°C, and the temperature of the secondary cold roller should be controlled at 10-20°C. These temperature ranges are to ensure that the film can maintain appropriate hardness and strength during the cooling process, while avoiding uneven film or cracking due to too low temperature. The specific setting of the temperature depends on the melting point of the polyethylene material used, the thickness of the film, and the required cooling rate.
[0058] Preferably, the temperature of the primary cold roller can be set to 25°C, and the temperature of the secondary cold roller can be set to 15°C. Such temperature settings can provide a good cooling effect while maintaining the uniformity and surface smoothness of the film.
[0059] More specifically, the temperature of the rollers can be precisely adjusted by installing temperature sensors and control systems to ensure temperature stability throughout the production process. As an alternative, water cooling or air cooling systems can also be used to assist roller cooling, which can more effectively control the cooling process of the film in high temperature or high humidity environments. In addition, the temperature settings of the rollers can be adjusted according to seasonal and environmental conditions to adapt to different production environments.
[0060] In some embodiments, in step S3, a β-ray thickness gauge is used to detect the film thickness, and the detection accuracy is ±0.001 mm.
[0061] It should be noted that the β-ray thickness gauge is an instrument used to measure the thickness of a film. It determines the thickness of the film by emitting β-rays and detecting the attenuation of the β-rays after they penetrate the film. This technology is widely used in the film industry due to its high accuracy and non-destructive testing.
[0062] Specifically, in step S3, a beta-ray thickness gauge is used to detect the film thickness with a detection accuracy of ±0.001 mm. This means that the beta-ray thickness gauge can measure small changes in the film thickness to ensure the consistency and quality control of the film. The choice of detection accuracy depends on the application requirements of the film and the demand for thickness control during the production process. For example, for applications that require strict thickness control to ensure barrier properties or mechanical strength, high-precision measurement is necessary.
[0063] Preferably, the beta-ray thickness gauge setup should include a calibration procedure to ensure the accuracy of the measurement results. More specifically, the thickness gauge should be calibrated regularly and verified using standard samples of known thickness to reduce measurement errors. As an alternative, in addition to the beta-ray thickness gauge, you can also consider using an X-ray thickness gauge or an ultrasonic thickness gauge. These devices can also provide high-precision thickness measurements and each has its own advantages. For example, an X-ray thickness gauge has better penetration for multi-layer films, while an ultrasonic thickness gauge is suitable for thicker films. In addition, multiple thickness gauges can be installed on the production line to achieve continuous monitoring of the film thickness, thereby further improving the control level of the production process and product quality.
[0064] In some embodiments, the aging treatment time in step S4 is 24-48 hours, the treatment environment temperature is 20-30° C., and the relative humidity is 40%-60%.
[0065] It should be noted that aging treatment is a heat treatment process used to stabilize the physical properties of polymer materials and reduce the internal stress generated during processing, thereby improving the durability and reliability of the product. The treatment environment temperature and relative humidity refer to the temperature and humidity conditions during the aging treatment process, which have an important impact on the stability and final performance of the material.
[0066] Specifically, in step S4, the aging treatment time is 24-48 hours, the treatment environment temperature is 20-30°C, and the relative humidity is 40%-60%. These parameters are set to ensure that the polyethylene film can release internal stress evenly during the aging treatment process, while avoiding the degradation of material properties due to excessively high temperature or low humidity. The specific settings of the aging treatment time, temperature and humidity depend on the thickness of the film, the type of material, and the expected application requirements.
[0067] Preferably, the aging treatment can be carried out in a controlled environment room to ensure the stability of temperature and humidity. More specifically, a constant temperature and humidity chamber can be used to perform the aging treatment, and the temperature and humidity in the chamber can be accurately adjusted by sensors and control systems.
[0068] Furthermore, as an alternative, if there are stricter requirements for the aging treatment time, accelerated aging treatment methods can be considered, such as shortening the treatment time by increasing the treatment temperature, but at the same time, it is necessary to ensure that the performance of the film is not affected. In addition, periodic temperature and humidity changes can also be used to optimize the aging treatment effect, such as adjusting the temperature and humidity in stages within 24 hours to meet the stress release requirements at different stages.
[0069] Example 1 A method for preparing an unstretched polyethylene film, comprising the following raw materials in the following mass ratios: 30% high-pressure polyethylene, 40% linear polyethylene, 25% metallocene polyethylene, and 5% anti-blocking agent; the first intermediate layer comprises 15% high-pressure polyethylene, 20% low-pressure polyethylene, 30% linear polyethylene, and 1% easy-to-process aid; the information molded aluminum plating layer comprises 10% high-pressure polyethylene, 8% linear polyethylene, 70% metallocene polyethylene, 6% anti-blocking agent, and 5% special additive.
[0070] The preparation method of this embodiment comprises the following steps: S1. The raw materials of each layer component are weighed according to the above mass ratio and mixed, and stirred evenly in a blender for 20 minutes; S2. The stirred raw materials are heated and plasticized until the raw materials are completely melted, and the heating and plasticization and T-die processing temperature are controlled at 200°C; S3. The plasticized resin is extruded forward through the screw of the extruder, and is extruded and laminated through a T-die to form a four-layer film; S4. After the extruded resin flows through the T-die, it flows to the main cold roller, the temperature of the main cold roller is controlled at 25°C, the temperature of the secondary cold roller is controlled at 15°C, and the cooling molding is performed; S5. Detect the thickness of the formed film using a β-ray thickness gauge with a detection accuracy of ±0.001mm, and adjust the film thickness according to the detection results; S6. The formed film is rolled up and subjected to aging treatment. The aging treatment time is 36 hours. The treatment environment temperature is controlled at 25° C. and the relative humidity is controlled at 50%.
[0071] In this embodiment, the main component of the anti-adhesion agent is organic synthetic silicon micro-spherical particles with a particle size of less than 5 microns to ensure that the film has good anti-adhesion performance. The special auxiliary agent is nano-scale silicon dioxide, which is used to improve the barrier performance of the film.
[0072] Experimental data: Synthesis method: Follow the above steps S1 to S6.
[0073] Reaction conditions: stirring time 20 minutes, heating plasticizing temperature 200℃, cooling molding temperature main cold roller 25℃, secondary cold roller 15℃, aging treatment time 36 hours, temperature 25℃, relative humidity 50%.
[0074] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0075] Performance test: The tensile strength, elongation at break and haze of the film all meet industrial standards. The adhesion of the aluminum coating is greater than 3N, and the peel strength after compounding with the PE film is greater than 3N on average.
[0076] Application and Effect: The unstretched polyethylene film prepared in this embodiment has good physical properties and high adhesion of the molded laser aluminum plating effect, and is suitable for high-end packaging materials, especially in occasions requiring high barrier properties and aesthetics. Experiments show that the film exhibits excellent durability and reliability in practical applications.
[0077] Example 2 A method for preparing an unstretched polyethylene film, comprising the following raw materials in the following mass ratios: 25% high-pressure polyethylene, 45% linear polyethylene, 20% metallocene polyethylene, and 5% anti-blocking agent; the first intermediate layer comprises 15% high-pressure polyethylene, 15% low-pressure polyethylene, 30% linear polyethylene, and 1% easy-to-process aid; the information molded aluminum plating layer comprises 15% high-pressure polyethylene, 10% linear polyethylene, 60% metallocene polyethylene, 5% anti-blocking agent, and 5% special additive.
[0078] The preparation method of this embodiment comprises the following steps: S1. The raw materials of the non-laser molded layer are weighed and mixed according to the above mass ratio and stirred evenly in a blender for 25 minutes; S2. The stirred raw materials are heated and plasticized until the raw materials are completely melted, and the heating and plasticization and T-die processing temperature are controlled at 220°C; S3. The plasticized resin is extruded forward through the screw of the extruder, and is extruded and laminated through a T-die to form a four-layer film; S4. After the extruded resin flows through the T-die, it flows to the main cold roller, the temperature of the main cold roller is controlled at 20°C, the temperature of the secondary cold roller is controlled at 15°C, and the cooling molding is performed; S5. Detect the thickness of the formed film using a β-ray thickness gauge with a detection accuracy of ±0.001mm, and adjust the film thickness according to the detection results; S6. The formed film is rolled up and subjected to aging treatment. The aging treatment time is 36 hours. The treatment environment temperature is controlled at 25°C and the relative humidity is controlled at 50%; S7. The non-laser molded layer is barrier coated with nano-aluminum oxide having a coating thickness of 0.2 microns to improve the barrier properties of the film.
[0079] In this embodiment, the main component of the anti-adhesion agent is organic synthetic silicon micro-spherical particles with a particle size of less than 5 microns to ensure that the film has good anti-adhesion performance. The special auxiliary agent is nano-scale silicon dioxide, which is used to improve the barrier performance of the film.
[0080] Experimental data: Synthesis method: Follow the above steps S1 to S7.
[0081] Reaction conditions: stirring time 25 minutes, heating plasticizing temperature 220℃, cooling molding temperature main cold roller 20℃, secondary cold roller 15℃, aging treatment time 36 hours, temperature 25℃, relative humidity 50%.
[0082] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0083] Performance test: The tensile strength, elongation at break and haze of the film all meet industrial standards. The oxygen permeability after barrier coating is reduced to 1 / 10 of that before coating, and the water vapor permeability is reduced to 1 / 5 of that before coating.
[0084] Use and Effect: The unstretched polyethylene film prepared in this embodiment has good physical properties and a high-adhesion molded laser aluminum plating effect, and also has excellent barrier properties, and is suitable for packaging materials requiring high barrier properties, especially in situations where the shelf life of the contents needs to be extended. Experiments show that the film exhibits excellent durability and reliability in practical applications, and can effectively extend the shelf life of the packaged contents.
[0085] Example 3 A method for preparing an unstretched polyethylene film, comprising the following raw materials in the following mass ratios: 25% high-pressure polyethylene, 40% linear polyethylene, 25% metallocene polyethylene, and 5% anti-blocking agent; the first intermediate layer comprises 15% high-pressure polyethylene, 20% low-pressure polyethylene, 30% linear polyethylene, and 1% easy-to-process aid; the information molded aluminum plating layer comprises 10% high-pressure polyethylene, 8% linear polyethylene, 65% metallocene polyethylene, 5% anti-blocking agent, and 5% special additive.
[0086] The preparation method of this embodiment comprises the following steps: S1. The raw materials of the non-laser molded layer are weighed and mixed according to the above mass ratio and stirred evenly in a blender for 30 minutes; S2. The stirred raw materials are heated and plasticized until the raw materials are completely melted, and the heating and plasticization and T-die processing temperature are controlled at 230°C; S3. The plasticized resin is extruded forward through the screw of the extruder, and is extruded and laminated through a T-die to form a four-layer film; S4. After the extruded resin flows through the T-die, it flows to the main cold roller, the temperature of the main cold roller is controlled at 25°C, the temperature of the secondary cold roller is controlled at 18°C, and the cooling molding is performed; S5. Detect the thickness of the formed film using a β-ray thickness gauge with a detection accuracy of ±0.001mm, and adjust the film thickness according to the detection results; S6. The formed film is rolled up and subjected to aging treatment. The aging treatment time is 48 hours. The treatment environment temperature is controlled at 28° C. and the relative humidity is controlled at 55%.
[0087] In this embodiment, the main component of the anti-adhesion agent is organic synthetic silicon micro-spherical particles with a particle size of less than 5 microns to ensure that the film has good anti-adhesion performance. The special auxiliary agent is nano-scale silicon dioxide, which is used to improve the barrier performance of the film.
[0088] Experimental data: Synthesis method: Follow the above steps S1 to S6.
[0089] Reaction conditions: stirring time 30 minutes, heating plasticizing temperature 230℃, cooling molding temperature main cold roller 25℃, secondary cold roller 18℃, aging treatment time 48 hours, temperature 28℃, relative humidity 55%.
[0090] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0091] Performance test: The tensile strength, elongation at break and haze of the film all meet industrial standards, and the thickness uniformity of the film is controlled within ±0.005mm.
[0092] Application and Effect: The unstretched polyethylene film prepared in this embodiment has good physical properties and a high-adhesion molded laser aluminum plating effect, and is suitable for high-end packaging materials, especially in occasions requiring high barrier properties and aesthetics. Experiments show that the film exhibits excellent durability and reliability in practical applications and can effectively extend the shelf life of the packaged contents.
[0093] Example 4 A method for preparing an unstretched polyethylene film, particularly including a barrier coating step, is composed of the following raw materials in the following mass ratios: 20% high-pressure polyethylene, 45% linear polyethylene, 25% metallocene polyethylene, and 5% anti-blocking agent; the first intermediate layer is composed of 15% high-pressure polyethylene, 20% low-pressure polyethylene, 30% linear polyethylene, and 1% easy-to-process aid; the information molded aluminum plating layer is composed of 15% high-pressure polyethylene, 10% linear polyethylene, 60% metallocene polyethylene, 5% anti-blocking agent, and 5% special additive.
[0094] The preparation method of this embodiment comprises the following steps: S1. The raw materials of the non-laser molded layer are weighed and mixed according to the above mass ratio and stirred evenly in a blender for 30 minutes; S2. The stirred raw materials are heated and plasticized until the raw materials are completely melted, and the heating and plasticization and T-die processing temperature are controlled at 220°C; S3. The plasticized resin is extruded forward through the screw of the extruder, and is extruded and laminated through a T-die to form a four-layer film; S4. After the extruded resin flows through the T-die, it flows to the main cold roller, the temperature of the main cold roller is controlled at 20°C, the temperature of the secondary cold roller is controlled at 15°C, and the cooling molding is performed; S5. Detect the thickness of the formed film using a β-ray thickness gauge with a detection accuracy of ±0.001mm, and adjust the film thickness according to the detection results; S6. The formed film is rolled up and subjected to aging treatment. The aging treatment time is 48 hours. The treatment environment temperature is controlled at 25°C and the relative humidity is controlled at 50%; S7. The non-laser molded layer is barrier coated with nano-aluminum oxide having a coating thickness of 0.3 microns to improve the barrier properties of the film.
[0095] In this embodiment, the main component of the anti-adhesion agent is organic synthetic silicon micro-spherical particles with a particle size of less than 5 microns to ensure that the film has good anti-adhesion performance. The special auxiliary agent is nano-scale silicon dioxide, which is used to improve the barrier performance of the film.
[0096] Experimental data: Synthesis method: Follow the above steps S1 to S7.
[0097] Reaction conditions: stirring time 30 minutes, heating plasticizing temperature 220℃, cooling molding temperature main cold roller 20℃, secondary cold roller 15℃, aging treatment time 48 hours, temperature 25℃, relative humidity 50%.
[0098] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0099] Performance test: The tensile strength, elongation at break and haze of the film all meet industrial standards. The oxygen permeability after barrier coating is reduced to 1 / 10 of that before coating, and the water vapor permeability is reduced to 1 / 5 of that before coating.
[0100] Use and Effect: The unstretched polyethylene film prepared in this embodiment has good physical properties and a high-adhesion molded laser aluminum plating effect, and also has excellent barrier properties, and is suitable for packaging materials requiring high barrier properties, especially in situations where the shelf life of the contents needs to be extended. Experiments show that the film exhibits excellent durability and reliability in practical applications, and can effectively extend the shelf life of the packaged contents.
[0101] Example 5 A method for preparing an aluminum-plated substrate based on an unstretched polyethylene film, comprising raw materials in the following mass ratios: 30% high-pressure polyethylene, 40% linear polyethylene, 20% metallocene polyethylene, and 6% anti-blocking agent; the first intermediate layer is composed of 18% high-pressure polyethylene, 20% low-pressure polyethylene, 30% linear polyethylene, and 0.5% easy-to-process additive; the information molded aluminum-plated layer is composed of 15% high-pressure polyethylene, 10% linear polyethylene, 70% metallocene polyethylene, 5% anti-blocking agent, and 5% special additive.
[0102] The preparation method of this embodiment comprises the following steps: S1. The raw materials of each layer component are weighed according to the above mass ratio and mixed, and stirred evenly in a blender for 25 minutes; S2. The stirred raw materials are heated and plasticized until the raw materials are completely melted, and the heating and plasticization and T-die processing temperature are controlled at 200°C; S3. The plasticized resin is extruded forward through the screw of the extruder, and is extruded and laminated through a T-die to form a four-layer film; S4. After the extruded resin flows through the T-die, it flows to the main cold roller, the temperature of the main cold roller is controlled at 20°C, the temperature of the secondary cold roller is controlled at 15°C, and the cooling molding is performed; S5. Detect the thickness of the formed film using a β-ray thickness gauge with a detection accuracy of ±0.001mm, and adjust the film thickness according to the detection results; S6. The formed film is rolled up and subjected to aging treatment. The aging treatment time is 48 hours. The treatment environment temperature is controlled at 25°C and the relative humidity is controlled at 55%; S7. An aluminum film layer is coated on the corona layer of the film. The thickness of the aluminum film layer is 100 nanometers, which is achieved by vacuum coating technology.
[0103] In this embodiment, the main component of the anti-adhesion agent is organic synthetic silicon micro-spherical particles with a particle size of less than 5 microns to ensure that the film has good anti-adhesion performance. The special additive is nano-scale silicon dioxide, which is used to improve the barrier performance of the film. The corona layer is formed on the surface of the film by corona treatment to increase the adhesion between the film and the aluminum film layer.
[0104] Experimental data: Synthesis method: Follow the above steps S1 to S7.
[0105] Reaction conditions: stirring time 25 minutes, heating plasticizing temperature 200℃, cooling molding temperature main cold roller 20℃, secondary cold roller 15℃, aging treatment time 48 hours, temperature 25℃, relative humidity 55%.
[0106] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0107] Performance test: The tensile strength, elongation at break and haze of the film all meet industrial standards. The adhesion of the aluminum coating is greater than 3N, and the peel strength after compounding with the PE film is greater than 3N on average.
[0108] Application and Effect: The unstretched polyethylene film aluminum-plated substrate prepared in this embodiment has good physical properties and a high-adhesion molded laser aluminum-plated effect, and is suitable for high-end packaging materials, especially in occasions requiring high barrier properties and aesthetics. Experiments show that the film exhibits excellent durability and reliability in practical applications, and can effectively extend the shelf life of the packaged contents.
[0109] Comparative Example 1 This comparative example is a traditional polyethylene film, which is made from the following raw materials in mass ratio: High-pressure polyethylene 40%, linear polyethylene 30%, metallocene polyethylene 20%, anti-blocking agent 10%; The method for preparing the polyethylene film comprises the following steps: (a) mixing the above raw materials according to the mass ratio and stirring them evenly in a blender; (b) heating and plasticizing the mixed raw materials until the raw materials are completely melted, and the heating and plasticizing temperature is controlled at 220° C.; (c) the plasticized resin is extruded forward through the screw of the extruder, and is extruded and laminated through a T-die to form a film; (d) After the extruded resin flows through the T-die, it flows to the primary cold roller, the temperature of which is controlled at 25°C, and the temperature of the secondary cold roller is controlled at 20°C, for cooling and molding; (e) Testing the thickness of the formed film and adjusting the film thickness according to the test results, using a β-ray thickness gauge with a test accuracy of ±0.002 mm; (f) The formed film is rolled up and subjected to aging treatment. The aging treatment time is 24 hours. The treatment environment temperature is 30° C. and the relative humidity is 60%.
[0110] Comparative Example 2 This comparative example is a traditional polyethylene film, which is made from the following raw materials in mass ratio: High-pressure polyethylene 35%, linear polyethylene 25%, metallocene polyethylene 30%, anti-blocking agent 5%; The method for preparing the polyethylene film comprises the following steps: (a) mixing the above raw materials according to the mass ratio and stirring them evenly in a blender; (b) heating and plasticizing the mixed raw materials until the raw materials are completely melted, and the heating and plasticizing temperature is controlled at 230° C.; (c) the plasticized resin is extruded forward through the screw of the extruder, and is extruded and laminated through a T-die to form a film; (d) After the extruded resin flows through the T-die, it flows to the primary cold roller, the temperature of which is controlled at 30°C, and the temperature of the secondary cold roller is controlled at 25°C, for cooling and molding; (e) Testing the thickness of the formed film and adjusting the film thickness according to the test results, using a β-ray thickness gauge with a test accuracy of ±0.002 mm; (f) The formed film is rolled up and subjected to aging treatment. The aging treatment time is 36 hours. The treatment environment temperature is 25° C. and the relative humidity is 50%.
[0111] Experimental example The polyethylene films prepared in Example 2 and Comparative Examples 1-2 were obtained respectively; The polyethylene film was used to perform performance tests, including tensile strength, elongation at break, haze, and barrier properties; wherein the film of Example 2 was tested 3 times, the film of Comparative Example 1 was tested 3 times, and the film of Comparative Example 2 was tested 3 times; Test method: (a) Tensile strength and elongation at break were tested according to ASTM D882. (b) Haze is tested according to ASTM D1003; (c) Barrier properties are tested according to ASTM F1249 standard; The test results are shown in Tables 1 to 4: Table 1 Tensile strength test results Group Average tensile strength (MPa) Standard Deviation Example 2 24.5 0.5 Comparative Example 1 18.0 0.6 Comparative Example 2 20.5 0.7 Table 2 Elongation at break test results Group Average elongation at break (%) Standard Deviation Example 2 450 10 Comparative Example 1 300 15 Comparative Example 2 350 12 Table 3 Haze test results Group Average haze (%) Standard Deviation Example 2 1.5 0.2 Comparative Example 1 3.0 0.3 Comparative Example 2 2.5 0.4 Table 4 Barrier performance test results Group Oxygen transmission rate (cc / m²·day) Water vapor transmission rate (g / m²·day) Example 2 0.8 2.0 Comparative Example 1 1.5 3.5 Comparative Example 2 1.2 2.8 From Tables 1 to 4, we can see that: Compared with the control example, the polyethylene film prepared by the technical solution of the present application performs better in terms of tensile strength, elongation at break, haze and barrier properties, especially the barrier properties. The polyethylene film prepared by the technical solution of the present application has lower oxygen permeability and water vapor permeability, showing a better barrier effect.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
[0113] The above descriptions are only some preferred embodiments of the present invention and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the embodiments of the present invention is not limited to the technical solutions formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the embodiments of the present invention.
Claims
1. An unstretched polyethylene film, characterized in that: It includes a four-layer composite structure, which are respectively a non-laser molded layer, a first intermediate layer, a second intermediate layer, and a laser molded aluminum-plated layer; The non-laser molded layer comprises high-pressure polyethylene, linear polyethylene, metallocene polyethylene and anti-blocking agent, and the mass percentage of the manufacturing components is: 10%-30% of high-pressure polyethylene, 20%-50% of linear polyethylene, 10%-30% of metallocene polyethylene and 4%-7% of anti-blocking agent that does not affect haze; The first intermediate layer and the second intermediate layer are made of the same material, and the components include high-pressure polyethylene, low-pressure polyethylene, and linear polyethylene, and the mass percentage of the manufacturing components is: high-pressure polyethylene 10%-20%, low-pressure polyethylene 5%-25%, metallocene polyethylene 20%-50%, and easy processing aid 0.5%-1%; The components of the molded aluminum plating layer include high-pressure polyethylene, metallocene polyethylene, anti-adhesive agent that does not affect haze and special additives, and the mass percentages of the manufacturing components are: high-pressure polyethylene 5%-20%, linear polyethylene 5%-10%, metallocene polyethylene 50%-90%, anti-adhesive agent that does not affect haze 4%-8%, and special additives 2%-8%.
2. The unstretched polyethylene film according to claim 1, characterized in that: The thickness ratios of the non-laser molded layer, the first intermediate layer, the second intermediate layer and the information molded aluminum film layer are: 20-30% for the non-laser molded layer, 20-35% for the first intermediate layer, 20-35% for the second intermediate layer, and 20-30% for the information laser molded aluminum layer.
3. The unstretched polyethylene film according to claim 1, characterized in that: The main component of the anti-adhesion agent is organic synthetic silicon micro-spherical particles.
4. The unstretched polyethylene film according to claim 1, characterized in that: If barrier properties are desired, the non-laser embossed layers may be barrier coated.
5. An aluminum-plated substrate based on the unstretched polyethylene film according to claim 1, characterized in that: The invention comprises an unstretched polyethylene film and an aluminum film layer, wherein the aluminum film layer is combined with the corona layer of the film.
6. A method for preparing the unstretched polyethylene film according to claim 1, comprising the following steps: S1. Prepare the raw materials of each layer component and stir them evenly, then heat and plasticize them to melt the raw materials, and then extrude the plasticized resin forward through the screw of the extruder, and extrude and laminate through the T-die according to the designed structural level, wherein the processing temperature of heating and plasticizing and the T-die is 165℃-245℃; S2. The extruded resin passes through the T-type die head and flows to the primary cold roller, where it is cooled and formed by the secondary cold roller; S3. Detect and control the thickness of the formed film; S4. Then roll it up and perform aging treatment.
7. The method for preparing an unstretched polyethylene film according to claim 6, characterized in that: The stirring time of each layer of raw materials in step S1 is 15-30 minutes.
8. The method for preparing an unstretched polyethylene film according to claim 6, characterized in that: In step S2, the temperature of the primary cold roller is 15-30°C, and the temperature of the secondary cold roller is 10-20°C.
9. The method for preparing an unstretched polyethylene film according to claim 6, characterized in that: In step S3, a β-ray thickness gauge is used to detect the film thickness, and the detection accuracy is ±0.001 mm.
10. The method for preparing an unstretched polyethylene film according to claim 6, characterized in that: The aging treatment time in step S4 is 24-48 hours, the treatment environment temperature is 20-30° C., and the relative humidity is 40%-60%.
Citation Information
Patent Citations
Reinforced aluminium-plated level undrawn polypropylene film and production process thereof
CN102372119A
Linear easy-tearing packaging-use unstretched aluminum-plated thin film
CN104129120A
Undrawn polyethylene film and preparation method thereof
CN106739359A
High-aluminizing-fastness BOPP base film for low-temperature laser mold pressing and preparation method thereof
CN111703159A